Design of integrated laser diode driver for 3D-depth sensing applications. (July 2021) - David, Romain; Allard, Bruno; Branca, Xavier; Joubert, Charles
Abstract: This paper presents the design and comparison of two integrated CMOS Laser Diode Drivers (LDD) intended for 3D-depth sensing applications used in mobile phones and based on the indirect Time-of-Flight (iToF) measurement. Architectures are based on known driver topologies where a standard DC/DC converter is connected to a switching element either in series or parallel to provide pulses. Two LDD prototypes have been implemented on-chip using a 130 nm CMOS technology from STMicroelectronics. Both prototypes are able to generate current pulses up to 3A with a 2.5ns pulse width at a maximum 200 MHz Pulse Repetition Frequency (PRF) under a 3.6V supply voltage. In these conditions, measurement results report an average output electrical power of 4.5W with an electrical efficiency of 58% and 62% for series and shunt configuration respectively.